High intracellular stability of the spidroin N‐terminal domain in spite of abundant amyloidogenic segments revealed by in‐cell hydrogen/deuterium exchange mass spectrometry. (20th December 2019) - Kaldmäe, Margit; Leppert, Axel; Chen, Gefei; Sarr, Medoune; Sahin, Cagla; Nordling, Kerstin; Kronqvist, Nina; Gonzalvo‐Ulla, Marta; Fritz, Nicolas; Abelein, Axel; Laίn, Sonia; Biverstål, Henrik; et al.
Abstract : Proteins require an optimal balance of conformational flexibility and stability in their native environment to ensure their biological functions. A striking example is spidroins, spider silk proteins, which are stored at extremely high concentrations in soluble form, yet undergo amyloid‐like aggregation during spinning. Here, we elucidate the stability of the highly soluble N‐terminal domain (NT) of major ampullate spidroin 1 in the Escherichia coli cytosol as well as in inclusion bodies containing fibrillar aggregates. Surprisingly, we find that NT, despite being largely composed of amyloidogenic sequences, showed no signs of concentration‐dependent aggregation. Using a novel intracellular hydrogen/deuterium exchange mass spectrometry (HDX‐MS) approach, we reveal that NT adopts a tight fold in the E. coli cytosol and in this manner conceals its aggregation‐prone regions by maintaining a tight fold under crowded conditions. Fusion of NT to the unstructured amyloid‐forming Aβ40 peptide, on the other hand, results in the formation of fibrillar aggregates. However, HDX‐MS indicates that the NT domain is only partially incorporated into these aggregates in vivo . We conclude that NT is able to control its aggregation to remain functional under the extreme conditions in the spider silk gland. Abstract : Intracellular protein folding. The N‐terminal domain (NT) from the spider silk protein MaSp1 is highly soluble and facilitates the expression of amyloid‐forming proteins. Here, we use intracellular hydrogen/deuterium exchange mass spectrometry to reveal that NT adopts a tight fold in the cytosol and protects its aggregation‐prone segments. NT is able to remain partially folded inside amyloid‐like aggregates, suggesting that its stability may play a role in spider silk assembly.